Media Pembelajaran IPS Berbasis Podcast: Studi Peluang Pemanfaatan dan Pengembangan di SMP Ibu Kartini Semarang - Zaenal Fathoni, Zaenal Fathoni; Husain, Fadly; Tri Atmaja, Hamdan (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Social studies is a subject that consists of various social sciences such as history, sociology, geography, etc., which makes the material quite dense. Social studies learning, which consists of various disciplines, makes some of the learning materials quite dense. Learning media can be an alternative to overcome the obstacles in delivering dense material efficiently. This study aims to analyze the use of podcasts as a medium for social studies learning and to analyze the opportunities for developing podcasts at Ibu Kartini Junior High School in Semarang. The method used in this study is a descriptive method with a qualitative approach through literature study, observation, and in-depth interviews. This research was analyzed using the cognitive theory of multimedia learning (Richard E. Mayer). This study found, based on a literature review, that podcasts are effective and efficient when used as a learning medium for social studies. Podcasts have the advantages of ease of access, transmission, and development of themes or materials that are relevant to the subject matter, interests, and characteristics of students. The social studies learning media used by teachers still have weaknesses, so they need to utilize or develop media that facilitate students in building initial understanding and reviewing dense social studies material flexibly. Teachers have the interest and motivation to utilize or develop podcast-based social studies learning media that are the original work of teachers and students who support the plan.